Prosedur Penerbitan Surat Permintaan Penjelasan Atas Data atau Keterangan(SP2DK) dalam Pengawasan Wajib Pajak - Dynda Hesta Monita; Rusnandari Retno Cahyani (Universitas Sahid Surakarta, 2018)
Government policies related to taxation have become one of the policies that have major challenges and concerns from the public, because most of the approximately 76% of development in Indonesia comes from the state budget, most of which are supported by tax revenues. Some things that cause taxpayers to obtain an appeal letter or SP2DK include data on assets owned by taxpayers who have never been reported in Annual Personal Income Tax Returns and the value added of buildings due to significant development that has the potential to be subject to VAT over activities build yourself. The Acoount Representative (AR) counseled the Taxpayers and gave a response as to why they did not pay taxes. Account Representative (AR) follows up on the taxpayer's response.